PHILOLOGICAL STUDY OF JALĀLAIN: Exegesis Manuscript of Kyai Nur Hisyam Mandirejo - Siti Mir'atul Af'idah (STAI AL-ANWAR SARANG, 2017)
Abstract The study of manuscript is one of the popular topics in the academical world. Especially for exegesis manuscript, it is rarely found in the archipelago. This research is important for preserving the cultural heritage in the form of manuscript. This article examines the codicological aspects of the manuscript. By using codicological discourse analysis, this research concludes that JalÄlain Exegesis Manuscript of Kyai Nur Hisyam Mandirejo was written on European paper. He wrote the manuscript into two volumes for studying and learning significance. He finished writing the first volume in 1269 H. and the second volume in 1361 H. The manuscript is still quite clear to read, while the paper has weathered and even there are some papers lost and broken. By using critical discourse analysis, this research reveals that the manuscript consists of various additional information, such as grammatical or naá¸wu explanation of certain words, stories related to certain sentences in the exegesis and ma'na gandhul pegon (interlinier text). By comparing the manuscript to JalÄlain Exegesis of printed version that corrected by Muá¸¥ammad Dhu al-Kifl Zain al-DÄ«n al-Waá¹anÄ«, it was printed by DÄr al-Kutub al-IslÄmiyyah on January 2011th M. / Muá¸¥arram 1432 H. The researcher reveals that both of them are similar text but have different main text for the guidelines copying process. Some differences found in several sides of study. This research concludes that there are three patterned errors of manuscript writing, like about the writing of Ù„Ø§, Ù‡ (ha`) and Ù‰ (alif layyinah).